Method validation of High Performance Liquid Chromatography for determination of mycolic acid profile of Mycobacterium tuberculosis - Asri Darmawati (RJPBCS, 2017)
This study developed the High Performance Liquid Chromatography (HPLC) for INH resistant M. tuberculosis (MTB) isolate identification based on a chromatogram profile of mycolic acids (MAs). The aim of this study was to validate the HPLC for determining the characteristic profile of MAs chromatogram of the INH resistant MTB. The optimum derivatization process obtained was as follows: the minimum biomass weight was 25 mg. The experimental temperature was performed in (80-90)o C using a water bath for minimum 30 minutes in order to complete the MAs derivatization. Reagent volume used in the range of (200-500 μL) were not influenced the MAs chromatogram profile. The optimum condition of HPLC was as follows: mobile phase was methanol:isopropanol (60:40) for 3 minutes, followed by gradient elution (4:96) in 50 minutes. Thereafter, the mobile phase composition change gradually for 40 minutes to a final composition of (60:40). The sample volume was 20 μL and the mobile phase flow rate was 1 mL/minute. The result of this study showed that the MAs chromatogram profile of INH resistant MTB looked like H37Rv MTB strain. The chromatogramp profile was a cluster with 6 characteristic peaks at the end of the analysis. The other short chain carbon fatty acids were eluted in the first 15 minutes.